A Civilian in Lawton's 1899 Philippine Campaign : The Letters of Robert D. Carter - Carter, Robert Dexter, 1876-1926 (American military experience series., 2013)
In the midst of the Philippine-American War, twenty-two-year-old Robert Dexter Carter served in Manila as a civilian quartermaster clerk. Through his letters to his family, he provided a vivid picture of army life in Manila--the sights, the smells, and his responses to the native culture. In addition to his letters, his diary and several related articles present a firsthand account of the historic voyage of the United States Army Transport Grant through the Suez Canal to Manila in early 1899. Carter's writings not only tell of his sometimes harrowing experiences, but also reveal the aspirations and fears of a young man not quite sure of his next steps on life's journey.